Cardiac myosin super relaxation (SRX): a perspective on fundamental biology, human disease and therapeutics - Manuel Schmid; Christopher N. Toepfer (Biology Open, 2021)
The fundamental basis of muscle contraction ‘the sliding filament model’ (Huxley and Niedergerke, 1954; Huxley and Hanson, 1954) and the ‘swinging, tilting crossbridge-sliding filament mechanism’ (Huxley, 1969; Huxley and Brown, 1967) nucleated a field of research that has unearthed the complex and fascinating role of myosin structure in the regulation of contraction. A recently discovered energy conserving state of myosin termed the super relaxed state (SRX) has been observed in filamentous myosins and is central to modulating force production and energy use within the sarcomere. Modulation of myosin function through SRX is a rapidly developing theme in therapeutic development for both cardiovascular disease and infectious disease. Some 70 years after the first discoveries concerning muscular function, modulation of myosin SRX may bring the first myosin targeted small molecule to the clinic, for treating hypertrophic cardiomyopathy (Olivotto et al., 2020). An often monogenic disease HCM afflicts 1 in 500 individuals, and can cause heart failure and sudden cardiac death. Even as we near therapeutic translation, there remain many questions about the governance of muscle function in human health and disease. With this review, we provide a broad overview of contemporary understanding of myosin SRX, and explore the complexities of targeting this myosin state in human disease. This article has an associated Future Leaders to Watch interview with the authors of the paper.